(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Specialists have recommended that fledgling teachers who have not invested energy in theclassroom might rely more upon different contributions to shape their assumptions for futureachievement .Intrinsic motivation and amotivation are two of the motivation factors that can influenceprocrastination. High procrastinators tend to have more amotivation and less intrinsic motivation, whichsuggests that students procrastinate because they lack the intrinsic intellectuality and innatepsychological need for competence, or because they do not have a sense of purpose or direction in theirlives. Neuroticism, conscientiousness, agreeableness, and extraversion are some of the personalityqualities that have been shown to have a role in procrastination. High procrastinators had higher levelsof neuroticism and agreeableness and lower levels of extraversion and conscientiousness. Laziness andpoor time management were determined to be the two most common causes of academicprocrastination, despite the fact that there was no difference between the causes of procrastinationreported by males and females. In any case, no researcher in India has conducted a systematic study onthe influence of gender and academic achievement on the self-efficacy, thinking, and dynamic styles ofimminent pre-service teachers as a whole.